MULTIMEDIA INTERAKTIF PENDIDIKAN ANAK USIA DINI - US, Harisa; Afandi, Nur Kholik; Murdani Z, Edy (TARBAWI:Journal on Islamic Education, 2023)
Early childhood is prime time, a very important time to provide the right stimulation to maximize growth and development, but there are still many teachers who ignore their parents. Age appropriate equipment is required. So that young children remain interested in learning, appropriate early childhood learning media are needed, one of which is interactive multimedia. This type of research is development research (RD). The data collection method uses . Observations, interviews, documentation, LKA tests. Data analysis includes testing, interactive multimedia design with power points and percentages, efficacy, descriptive analysis. Findings: (1) interactive multimedia design in Early Childhood learning, (2) interactive multimedia is effective in pre-test evaluation as seen in the results, the learning process in the classroom achieved an average of 80% complete learning outcomes from 2.07 to 2.73 posttest, increased significantly from 2.73 to after the test, from a total of 50 respondents with a standard deviation of 0.799 before the test increased a standard deviation of 0.438.